Comparative study of structural and magnetic properties of Ni and La substituted calcium hexaferrite - V. S. Shinde; S. G. Dahotre (Cerâmica, 2021)
Abstract Ni and La substituted M-type Ca hexaferrite of composition CaNi1Fe11O19 and CaLa1Fe11O19 were synthesized by sol-gel auto combustion method using metal nitrates as oxidants and citric acid as reducing agent. The prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), energy dispersive X-ray analysis (EDAX), and vibrating sample magnetometry (VSM). XRD study revealed that both samples had lattice parameters a and c within the range of M-type hexaferrite. The SEM micrographs displayed grains having irregular shapes and sizes in the nanometer range. FTIR peaks confirmed the structure of M-type hexaferrite. EDAX spectra showed the homogeneous distribution of ions in both samples. In CaNi1Fe11O19, we found saturation magnetization (Ms) of 12.18 emu/g and coercivity (Hc) of 193.2 Oe. On the other hand, in CaLa1Fe11O19, we found Ms of 0.55 emu/g and Hc of 404.4 Oe. Saturation magnetization and coercivity values obtained for La substituted M-type Ca hexaferrite are suitable for low-density magnetic recording devices.